Effect of different K:Na ratios in soil on dispersive charge, cation exchange and zeta potential. (13th November 2018) - Farahani, E.; Emami, H.; Fotovat, A.; Khorassani, R.
Summary: The role of potassium (K) in clay dispersion in agricultural soils containing large concentrations of K could be similar to Na. This research was carried out to assess the effect of potassium to sodium ratios (K:Na) on net dispersive charge, Gapon selectivity coefficient ( K G ), zeta potential ( ζ ) and percentage of dispersible clay. Different K:Na ratios at two electrical conductivity levels (EC = 3 and 6 dS m −1 ) were added to an agricultural loamy soil. The results demonstrated that the net dispersive charge and percentage of dispersible clay showed positive relations with K concentration and K:Na ratio; also, the percentage of dispersible clay and net dispersive charge had a positive correlation, at both EC levels. Therefore, net dispersive charge as well as percentage of dispersible clay can show the degrading effect of K on soil structure. The K G values for K ( K G(K) ) were larger than those of Na ( K G(Na) ) because of large cation selectivity for K in soil. Neither K G(K) nor K G(Na) had a significant effect on the percentage of dispersible clay, but they did influence net dispersive charge, indicating that the status of cation exchange might affect dispersive charge of the soil. At both EC levels, absolute amounts of ζ, as an index of diffuse double layer (DDL) thickness, increased with increasing concentrations of monovalent cations (especially K). In addition, a strong positive correlation was observed between the dispersive charge and ζ . Our results demonstrated that K could affect soil structure because of a change in cation selectivity, with K increasing repulsive forces among clay particles and creating dispersion. Highlights: K created repulsive forces between clay particles that led to clay dispersion. Net dispersive charge and dispersible clay increased with increasing K concentration and K:Na ratio. Cation exchange status ( K G values) affected soil net dispersive charge significantly. A positive correlation between dispersive charge and zeta potential was observed.